Human Enteric Glial Cells Alleviate Damaged Adult Sensory Neurons in Rats - Shah, Dhara; Jiang, Cai; Reddy, Kiran; Su, Caixin; Jiang, Shucui (The Meducator, 2013)
Spinal cord injury affects millions across the globe. Little is known regarding the cellular mechanism of injury and, unfortunately, there are few viable treatment options. One potential option is the transplantation of peripheral nerves into the site of injury. The complicating factor is that the peripheral nervous system is not readily accessible, and thus the procedure introduces the risk of disrupting the function of other areas. However, this risk is minimized if the nerves are extracted from the enteric system, which is embedded in the lining of the gastrointestinal tract. This system bears similarities to the central nervous system, has remarkable plasticity, and releases growth factors that not only facilitate regeneration of neurons but also protect the enteric nervous system from damage. Previous research shows that rat enteric glial cells induce regeneration in rodent neurons in vivo with a crushed spinal cord, and in vitro to dorsal root ganglia treated with semaphorin-3A to mimic spinal cord injury. We examined whether human enteric glia demonstrate similar effects in vitro on rodent dorsal root ganglia. Our experiments to date show that this treatment is viable, emphasizing its use in clinical trials. The success of this technique is largely due to the fact that the donor cells originate from the host, which minimizes the chance of rejection.